Weight changes during chemotherapy and prognostic outcome in breast cancer: A preliminary assessment in single centre cohort - Lua, Pei Lin; Zakaria, Noor Salihah; Mamat, Nik Mazlan (Malaysian Public Health Physicians’ Association, 2016)
A concern in breast cancer involves changes in weight which may adversely affect the prognosis of patients. This study intended to evaluate weight changed uring chemotherapy and its association with prognostic outcome measured as event-free survival (EFS)among breast cancer patients. A total of63 women diagnosed with breast cancer and have been treated by anthracycline-based chemotherapy between 2005 and 2011were included.A weight change (WC) was calculated based on relative percentage of weight changes from baseline to post-chemotherapy and categorized into either weight change (WC >5%) or stable (±5% WC).Survival probabilities were estimated using the Kaplan-Meier (SPSS 20). Upon treatment completion, 42.9% of the women experienced weight changes. A small weight reduction was observed (61.1 ± 11.6kg to 60.2 ± 11.9kg; -0.8 ± 4.0kg; p=0.106). The median EFS of women who experienced weight change was shorter (median 61.0 months) compared to those who maintained their weight (median 89.0 months) (p=0.044). In this study, weight changes during breast cancer chemotherapy were associated with poorer prognosis in comparison to women who maintained their weight.